Running great meetings & workshops for dummies - Pryce-Jones, Jessica; Lindsay, Julia (--For dummies., 2014)
This book provides clear group leadership instructions with immediate applications to employees in any department. Regardless of the type of meeting, training session or workshop you're running, this book provides the information you need.